2021
DOI: 10.1096/fj.202002730r
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and phospholipidomic characterization of extracellular vesicles inducing tumor microenvironment in Epstein‐Barr virus‐associated lymphomas

Abstract: Epstein-Barr virus (EBV) causes malignant carcinomas including B cell lymphomas accompanied by the systemic inflammation. Previously, we observed that phosphatidylserine (PS)-exposing subset of extracellular vesicles (EVs) secreted from an EBV strain Akata-transformed lymphoma (Akata EVs) convert surrounding phagocytes into tumor-associated macrophages (TAMs) via induction of inflammatory response, which is in part mediated by EBV-derived micro RNAs. However, it is still unclear about EV-carried other potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…An immunosuppressive TME exists in most EBV-associated tumors, which impedes the efficacy of immunotherapies ( 119 ). The majority of previous studies have confirmed that exosomes derived from EBV + tumor cells serve a role in inhibiting body immunity and promoting tumor cell immune evasion in the process of tumor progression ( 63 , 95 , 104 ). Therefore, targeting EBV + exosomes is considered as a promising new treatment for EBV + tumors.…”
Section: Future Perspectives: Exosomes Could Be Utilized As a New Therapeutic Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…An immunosuppressive TME exists in most EBV-associated tumors, which impedes the efficacy of immunotherapies ( 119 ). The majority of previous studies have confirmed that exosomes derived from EBV + tumor cells serve a role in inhibiting body immunity and promoting tumor cell immune evasion in the process of tumor progression ( 63 , 95 , 104 ). Therefore, targeting EBV + exosomes is considered as a promising new treatment for EBV + tumors.…”
Section: Future Perspectives: Exosomes Could Be Utilized As a New Therapeutic Methodsmentioning
confidence: 96%
“…The proteins or nucleic acids encoded by EBV may serve pivotal roles in tumorigenesis and tumor development as tumor regulators. In addition, exosomes serve essential roles in the transfer of oncogenic molecules, as well as in the tumorigenesis and tumor metastasis of EBV-associated tumors ( 62 , 63 ).…”
Section: Ebv Expresses Multiple Oncogenic Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass spectrometric and phospholipidomic analysis revealed that several immunomodulatory proteins and lipid mediators containing EVs are important for inducing the tumor microenvironment in EBV-positive lymphoma. 80 Exosome-mediated establishment of a tumor-supporting environment has been reported. Waldenström macroglobulinemia, which is characterized by a mutation in the innate immune-signaling adaptor myeloid differentiation response 88 (MyD88), was reported to secrete a mutant of MyD88 in EVs.…”
Section: Lymphoid Malignancy and Exosomesmentioning
confidence: 99%